REPRESENTASI SIMBOL HUBUNGAN MANUSIA DAN ALAM MELALUI EKOKRITIK SASTRA PADA NOVEL 3726 MDPL KARYA NURWINA SARI - Eva Apriani; Elsa Mulya Karlina (JIP: Jurnal Ilmu Pendidikan, 2025)
This research is entitled " Symbolic Representation of the Relationship Between Humans and Nature Thorough Literary Ecocriticsm in the Novel 3726 MDPL by Nurwina Sari".  Where this research aims to describe the symbolic representation of the relationship     between humans and nature in the novel 3726 MDPL by Nurwina Sari. The method used   in this research is a qualitative approarch, this refers to a research approach that produces descriptive data in the form of written data resulting from observing an object, namely a novel. The definition of qualitative research is research that is descriptive and analytical. Descriptive in qualitative research is presenting data or information objectively and factually, while analysis is interpretation, assessment, information or data in order to gain understanding. And the results of this research show that there are several quotes in the novel 3726 MDPL by Nurwina Sari that show symbols of relationships and nature.